PENGARUH PROGRAM PEMBELAJARAN KARAKTER TERHADAP PENURUNAN FREKUENSI KENAKALAN MINOR DI SD NEGERI 69 GALESONG 1 - Indah Trinawati; A.Ade Sigit Prasatya; St. Mustainah; Nural Miftahul Jannah; Amri Amal; Ichsan Muliawan (STKIP Subang, 2025)
This study aims to determine the effect of a character education program on reducing the frequency of minor delinquency at SDN 69 Galesong 1. This study is expected to provide information on the effectiveness of character education programs in reducing minor delinquency in students. Based on Bronfenbrenner's developmental ecology theory, this study highlights the importance of understanding the ecological context of adolescents in designing effective character education programs. Factors in the environment such as family, school, and society can influence adolescent behavior. Therefore, the implementation of character education in the school environment is crucial to forming positive values and morals that can overcome juvenile delinquency.